EFEKTIVITAS METODE MNEMONIK TERHADAP DAYA INGAT SISWA PADA MATA PELAJARAN IPS KELAS V DI SDN KUTABUMI II KAB. TANGERANG - Indah Rizki (Universitas Muhammadiyah Gresik, 2020)
This study aims to determine whether there are differences in the memory of students who are given the mnemonic method with students who are given conventional methods in class V social studies subjects. The hypothesis proposed in this study is.